Paroxysmal Tonic Upgaze - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2005)
This oculomotor syndrome of childhood, originally termed "benign paroxysmal tonic upgaze of childhood" (Ouvrier and Billson, 1988) is reviewed from the Children's Hospital of Westmead, Sydney, NSW, Australia.